FACTORS RELATED TO THE INCIDENCE OF ASPHYCIA IN NEW BORN INFANTS AT RSUD SUBULUSSALAM CITY - Putri Mika Hutari Ningsih; Marniati; Dian Fera; Susy Sri Wahyuni (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2023)
Asphyxia in newborns is a condition where the baby cannot breathe spontaneously and regularly immediately after birth. Data from Subulussalam City Hospital in 2021 there are 19 cases of newborn deaths with 8 cases of asphyxia. The purpose of this study was to analyze the factors associated with the incidence of asphyxia in newborns at Subulussalam City Hospital. In this study using a type of quantitative research with cross sectional design. The location of this research was carried out at the Subulussalam City Hospital, to be precise, in the perinatology room. This research was carried out in January-November 2022. The sample in this study was 34 respondents using the total sampling technique. The types of data used are primary data and secondary data. The results of the study showed that out of 34 cases of asphyxia, p=0.006 for maternal age, p=0.015 for gestational age, p=0.039 for normal weight, p=0.063 for infant condition, p value <0.05) meaning that there is a relationship between maternal age, gestational age, birth weight with the incidence of asphyxia in newborns at Subulussalam City Hospital. The conclusion from the results of the research carried out at Subulussalam City Hospital, it can be concluded that the p-value <0.05 has a significant relationship to the incidence of asphyxia in newborns which has been tested based on the chi square test SPSS analysis. It is recommended that it is necessary to increase socialization by health workers to mothers regarding diseases and complications that can arise during pregnancy, childbirth and postpartum as a preventive measure against the occurrence of asphyxia in newborns.